Current Understanding of RANK Signaling in Osteoclast Differentiation and Maturation - Park, Jin Hee (Mol Cells, 2017)
Osteoclasts are bone-resorbing cells that are derived from hematopoietic precursor cells and require macrophage-colony stimulating factor and receptor activator of nuclear factor-κB ligand (RANKL) for their survival, proliferation, differentiation, and activation. The binding of RANKL to its receptor RANK triggers osteoclast precursors to differentiate into osteoclasts. This process depends on RANKL-RANK signaling, which is temporally regulated by various adaptor proteins and kinases. Here we summarize the current understanding of the mechanisms that regulate RANK signaling during osteoclastogenesis. In the early stage, RANK signaling is mediated by recruiting adaptor molecules such as tumor necrosis factor receptor-associated factor 6 (TRAF6), which leads to the activation of mitogen-activated protein kinases (MAPKs), and the transcription factors nuclear factor-κB (NF-κB) and activator protein-1 (AP-1). Activated NF-κB induces the nuclear factor of activated T-cells cytoplasmic 1 (NFATc1), which is the key osteoclastogenesis regulator. In the intermediate stage of signaling, the co-stimulatory signal induces Ca(2+) oscillation via activated phospholipase Cγ2 (PLCγ2) together with c-Fos/AP-1, wherein Ca(2+) signaling facilitates the robust production of NFATc1. In the late stage of osteoclastogenesis, NFATc1 translocates into the nucleus where it induces numerous osteoclast-specific target genes that are responsible for cell fusion and function.